Answer:
0.63
Step-by-step explanation:
To get the relative frequency of students with red hair, we need to find the relative frequency of students with red hair from the students with gray eyes.
Since we already know that the total number of students with gray eyes is 35 and the number of red hair students with gray eye is 22
The formula we will use to calculate the relative frequency will be
The relative frequency of students with red hair = Total students of red hair with gray eyes divide by total number of gray eye students
22 ÷ 35 = 0.628 ≅ 0.63
Answer:
a
Step-by-step explanation:
Answer:
m= rise/ run
Step-by-step explanation:
We can find the slope by
m= rise/ run
= change in y/ change in x
= ( y2-y1)/(x2-x1)
= vertical change/ horizontal change
10 equal parts. that is the answer
Answer:
We conclude that (4, 2) is NOT a solution to the system of equations.
Step-by-step explanation:
Given the system of equations
![y = x - 2](https://tex.z-dn.net/?f=y%20%3D%20x%20-%202)
![y = 3x + 4](https://tex.z-dn.net/?f=y%20%3D%203x%20%2B%204)
Important Tip:
- In order to determine whether (4, 2) is a solution to the system of equations or not, we need to solve the system of equations.
Let us solve the system of equations using the elimination method.
![\begin{bmatrix}y=x-2\\ y=3x+4\end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7Dy%3Dx-2%5C%5C%20y%3D3x%2B4%5Cend%7Bbmatrix%7D)
Arrange equation variables for elimination
![\begin{bmatrix}y-x=-2\\ y-3x=4\end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7Dy-x%3D-2%5C%5C%20y-3x%3D4%5Cend%7Bbmatrix%7D)
Subtract the equations
![y-3x=4](https://tex.z-dn.net/?f=y-3x%3D4)
![-](https://tex.z-dn.net/?f=-)
![\underline{y-x=-2}](https://tex.z-dn.net/?f=%5Cunderline%7By-x%3D-2%7D)
![-2x=6](https://tex.z-dn.net/?f=-2x%3D6)
Now, solve -2x = 6 for x
![-2x=6](https://tex.z-dn.net/?f=-2x%3D6)
Divide both sides by -2
![\frac{-2x}{-2}=\frac{6}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B-2x%7D%7B-2%7D%3D%5Cfrac%7B6%7D%7B-2%7D)
Simplify
![x=-3](https://tex.z-dn.net/?f=x%3D-3)
For y - x = -2 plug in x = -3
![y-\left(-3\right)=-2](https://tex.z-dn.net/?f=y-%5Cleft%28-3%5Cright%29%3D-2)
![y+3=-2](https://tex.z-dn.net/?f=y%2B3%3D-2)
Subtract 3 from both sides
![y+3-3=-2-3](https://tex.z-dn.net/?f=y%2B3-3%3D-2-3)
Simplify
![y=-5](https://tex.z-dn.net/?f=y%3D-5)
The solution to the system of equations is:
(x, y) = (-3, -5)
Checking the graph
From the graph, it is also clear that (4, 2) is NOT a solution to the system of equations because (-3, -5) is the only solution as we have found earlier.
Therefore, we conclude that (4, 2) is NOT a solution to the system of equations.